The Effect of Health Education on Client Knowledge About Prevention of Hypertension - Tobing, Jack Robertus; Tuegeh, Johana; Bobaya, Janbonsel; Djafar, Nurseha S.; Kiling, Maykel Alfian; Kusmiyati, Kusmiyati (Jurnal Ilmiah Perawat Manado (Juiperdo), 2023)
Background: Hypertension is a condition where a person experiences an increase in blood pressure, which results in an increase in morbidity and mortality. The purpose of the study was to determine the effect of health education on client knowledge about the prevention of hypertension. Methods: This study uses a type of literature review research, namely a study in the form of a literature review using the results of previous studies as well as textbooks or research journals. To obtain data that is in accordance with the topic, researchers conducted a search for national and international-based journals on two data bases, namely PubMed and Google Schoolar using the keywords health education, knowledge of hypertension, prevention of hypertension. The keywords used are listed in each journal title obtained, with the provisions of the journals searched since 2011-2020. The results obtained were 5 journals used for literature review. Conclusion: there is an effect of health education on client knowledge about hypertension prevention.